The Brain and Religion: How Do They Relate to Each Other? - Reich, K Helmut (Intellectual Discourse, 2010)
This essay evolves around three concepts: (i) brain, (ii) religion, and (iii) relationship. Much of current misunderstandings and disputes result from using these concepts in differing ways without making the differences clear. Therefore, the stage is set with the corresponding definitions and a brief summary of the present state of affairs as understood here. That will also indicate the comparatively narrow content-related limits of the present considerations, which, from an enlarged perspective, are embedded in much wider concerns. Having thus situated the area under discussion here, two current major issues will be dealt with: “Is the brain the generator of religion,” and “Is the brain sufficient as a guide for living a satisfactory life?” Present answers are, respectively “Scientifically speaking, more data are needed before coming to a definite conclusion,” and “No.” In making the relevant arguments and statements, I partly draw on my earlier work.